An experimental and computational approach to pH‐dependent self‐aggregation of poly(2‐isopropyl‐2‐oxazoline). Issue 4 (19th December 2018) - Cagli, Eda; Yildirim, Erol; Yang, Shuo‐Wang; Erel‐Goktepe, Irem
ABSTRACT: Besides temperature, self‐aggregation of poly(2‐isopropyl‐2‐oxazoline) (PIPOX) can also be triggered via pH in aqueous solution (25 °C, pH > 5). Lowest energy structures and interaction energies of PIPOX with H3 O +, OH −, and H2 O were calculated by DFT methods showed that, in addition to their ability to protonate PIPOX, H3 O + ions had strong interaction with both water and PIPOX in acidic conditions. H3 O + ions acted as compatibilizer between PIPOX and water and increased the solubility of PIPOX. OH − ions were found to have stronger interaction with water compared to PIPOX resulting in desorption of water molecules from PIPOX phase and decreased solubility, leading to enhanced hydrophobic interactions among isopropyl groups of PIPOX and formation of aggregates at high pH. Results concerning the effect of end‐groups on aggregate size were in good agreement with statistical mechanics calculations. Moreover, the effect of polymer concentration on the aggregate size was examined. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2019, 57, 210–221 Abstract : Besides temperature, self‐aggregation of poly(2‐isopropyl‐2‐oxazoline) (PIPOX) can also be triggered via pH in aqueous solution above pH 5 at 25 °C. pH‐induced self‐assembly of PIPOX was characterized using dynamic light scattering, scanning electron microscopy imaging, and fluorescence spectroscopy techniques. The mechanism of self‐assembly was examined using DFT methods. PIPOX end group and concentration of PIPOX solution were found to be critical to the PIPOX aggregate size.